The Persistent Peril of the Artificial Slave. - LaGrandeur, Kevin (Science Fiction Studies, 2011)
This article surveys and analyzes the pre-industrial history of artificial humanoid servants and their historical persistence. The idea of artificial slaves—and questions about their tractability—is present not only in the literature of modern times but also extends all the way back to ancient Greek sources; and it is present in the literature and oral history of the Middle Ages and Renaissance as well. Furthermore, at each of these intervals, this idea is connected with an emotional paradox: the joy of self-enhancement is counterpoised with the anxiety of self-displacement that comes with distribution of agency. The idea of rebellious and dangerous artificial slaves is an archetype that spans Western history and persists not only in the pre-modern and modern imaginations, via stories about rebellious AI servants, but also in ancient scientific accounts and in modern systems theory, which is the basis for real AI.